COMPARISON OF EFFICACY OF TRADITIONAL AND MODERN MEDICINE IN DIABETES MELLITUS MANAGEMENT - Doby Indrawan; Iwal Reza Ahdi, Zainabur Rahmah (Adisam Publisher, 2024)
Diabetes mellitus is a chronic disease with an increasing prevalence globally. Diabetes management involves a multifaceted approach that includes lifestyle changes, blood sugar monitoring, and the use of medications. While modern medicine has become fundamental in the management of diabetes, traditional medicine is also still widely used. This study aims to evaluate and compare the efficacy of traditional and modern medicine in the management of diabetes. The research method used in this study is literature review. The results showed that modern medicine, which is based on strong scientific evidence and clinical validation, consistently showed higher efficacy in controlling blood sugar and reducing the risk of diabetes complications compared to traditional medicine. Drugs such as Metformin, DPP-4 inhibitors, and GLP-1 analogs have strong evidence of efficacy. On the other hand, studies on traditional medicine show mixed results with some offering potential benefits in controlling blood sugar. However, evidence regarding traditional medicine often lacks consistency and is poorly understood in the context of a clear mechanism of action.